Imagen corporal, estado nutricional y riesgo de ortorexia nerviosa en jóvenes usuarios de cinco centros de entrenamiento fitness de la ciudad de Iquitos, 2023 - Melendez Reategui, Xiomara Xibelly (2024)
The objective of the research was to determine the relationship between body image, nutritional status and the risk of orthorexia nervosa. The study was quantitatively focused, the type of work was descriptive, with a non experimental design and cross-sectional data collection. The sample consisted of 397 users of four fitness training centers. The stunkard scale, the body satisfaction and risk of orthorexia nervosa questionnaire, and a nutritional evaluation form were used as data collection instruments. Descriptive and inferential statistics were used to process the data collected. Studies report that 98.7% are satisfied with their body image, On the other hand, 36% have a normal nutritional status, 54.9% are overweight, 8.1% are obese grade i and 1% are obese grade ii. 4.3% have a high risk of orthorexia, 61.5% have no risk and 34.3% have a low risk. concluding that no statistically significant correlation was found between the study variables.